Sweetato creamer - Razali, Mohamad Azli; Din, Norrina; Zainol, Noorliza; Rezo, Khairul Hidayat (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
SweeTato Creamer is an innovative, plant-based powdered creamer crafted from nutrient-rich sweet potatoes and coconut milk powder, offering a naturally sweet and creamy alternative for beverages. Sweetened with stevia, it delivers a delicious flavor without added sugars, making it ideal for health-conscious consumers. This non-dairy, vegan-friendly product is rich in fiber, vitamins, and antioxidants, particularly vitamin A, supporting immune health and vision. Designed to address the growing demand for functional, clean-label foods, SweeTato Creamer redefines traditional creamers by leveraging the nutritional potential of sweet potatoes, an underutilized superfood. It promotes sustainability by supporting local agriculture and reducing reliance on processed ingredients. SweeTato Creamer caters to global trends for plant-based, low-sugar, and lactose-free alternatives, with significant potential for commercialization in the retail and health sectors. Its unique nutrient profile and convenience as a shelf-stable product make it an impactful addition to the food industry, fostering innovation, health-conscious living, and socio-economic growth